Multicultural Education in Fostering Tolerance Within Higher Education Environments - Alyssa Fairus Nur Islamy; Dava Rayyan Fayshal; Muhammad Amrum Kholid; Zaqila Putri Azizah; Eva Iryani (Fakultas Agama Islam, 2026)
Multicultural education is an educational approach that emphasizes respect for diversity in culture, religion, ethnicity, and social background within society. In the context of higher education, student diversity is a social reality that requires prudent management to prevent the emergence of conflict, discrimination, and intolerance. This study aims to analyze the role of multicultural education in shaping and enhancing students’ attitudes of tolerance within the higher education environment. The study employs a qualitative approach using library research methods, involving the analysis of various scientific journals, books, documents, and research findings relevant to multicultural education and tolerance. The results indicate that multicultural education plays a significant role in fostering students’ critical awareness of the importance of respecting differences, reinforcing values of inclusivity, and enhancing cross-cultural social interaction skills. The implementation of multicultural education can be achieved through the integration of diversity values into the curriculum, the strengthening of academic and non-academic activities, cross-cultural dialogue, and the creation of an inclusive and democratic campus culture. Thus, multicultural education plays a strategic role in realizing a harmonious, tolerant, and civilized higher education environment within a multicultural society.